Analisis Terhadap Diskriminasi Rasial dan Etnis Yang Terkait Dengan Hak Asasi Terhadap Manusia - Faturohman Faturohman; Emanuel Suhardi; Rosyd wardan (Lembaga Pengembangan Kinerja Dosen, 2024)
By enacting legislation to protect, maintain and monitor the importance of human rights. Discrimination refers to unfair or unequal treatment of a person or group based on certain characteristics.Such as injustice regarding race, ethnicity, gender, religion, sexual orientation, or disability. This usually occurs in environments such as education, health services, residence and in social interactions. Ethnic discrimination occurs when individuals or groups are judged based on their ethnic origin, which includes cultural identity, language, or national origin. This ethnic discrimination can lead to unequal treatment in terms of economic opportunities, access to health services, or unfair treatment by related institutions. In Indonesia, racial and ethnic discrimination is also a problem faced, although in a different context from other countries. Even though Indonesia has rich cultural, linguistic and ethnic diversity, there are still challenges in ensuring fair treatment for all citizens. Several ethnic minority groups in Indonesia may face various obstacles in terms of access to quality education, decent work and adequate health services.